Analisa Terhadap Kemampuan Penalaran Aljabar Dan Math Anxiety Antara Siswa yang Mengikuti Pembelajaran 7E Learning Cycle dan Concept Attainment - Khairani Khairani; Wahyudin Wahyudin; Endang Cahya (JURNAL EKSAKTA PENDIDIKAN (JEP), 2022)
Algebraic reasoning is one of mathematics ability that becomes goal of mathematics learning and to gain that goal, teachers need to cope the hindrance such as math anxiety. The objective of study is to analyze the attainment and escalation of algebraic reasoning in students who studied through 7E Learning Cycle and Concept Attainment, based on learning model and prior mathematical ability, in term of overall and in each class, along with math anxiety of students. The method is quasi-experimental pre-test-post-test-two-treatment designs. The samples were seventh grade junior high school students in Bandung that were consist of two classes with 40 students in 7E Learning Cycle class and 38 students in Concept Attainment class. Research’s result shows that there no significance difference of the attainment and escalation of algebraic reasoning in two experiment class based on learning model and category of early mathematical ability. But there is significance difference of the escalation of algebraic reasoning based on category of early mathematical ability in each experiment class. Besides, there is found that students have math anxiety when facing mathematics’ evaluation and tasks; and when math is involved to their future.